The Prognostic Value of FoxP3+ Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+ Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been suggested as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the “immune-desert” phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In “inflamed” tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry can act as an instrument to identify tumours infiltrated by functionally differing FoxP3+ T cell subtypes.